Primerjava vrednot smucarskih skakalcev - Križaj, J.; Ulaga, M.; Vodicar, J.; Jošt, B. (Kinesiologia Slovenica, 2018)
The aim of the study was to compare the values of ski jumpers in two different samples at different times. The sample of ski jumpers from year 2005 included 112 participants, and the sample of ski jumpers from year 2015 included 134 participants. The entire sample of ski jumpers (n = 246) was divided into three age groups: children aged 12 to 14 years, juniors aged 15 to 17 years, and seniors aged 18 years and older. The respondents were asked to rate the importance of 68 statements which expressed their motives for sports participation by using a five-point Likert scale. The results demonstrated high variability in the mean rankings acquired from the complete sample of ski jumpers. The correlation coefficient between the mean values of all statements (n= 68) for the year 2005 to 2015 was high and statistically significant (r = .82, p < .01). High and statistically significant correlations (p < .01) were also found for all three age groups of ski jumpers. Characteristic differences of specific value statements (p < .05) from 2005 to 2015 were only found for five value statements. In 2005 the study, conducted in three age groups of athletes, showed statistically significant differences in seven statements. In 2015 statistically significant differences between the age groups of ski jumpers were found in 25 value statements. Considering the increase in differences in 2015, we can conclude that the differences in the importance of specific values between age groups increase with time and maturation.